The Adequate Selection Algorithm by Estimating Local Oxide Influence - Andriukaitis, D. (Elektronika ir Elektrotechnika, 2010)
During oxidation impurities in a integrated circuit can change its electrical, chemical, and even mechanical properties. Redistribution of impurities in the thermal process is very important for the production of three dimensional integrated structures of increasingly higher integration degree, impurities move to other areas or redistribute because of the thermal process, error occurs in the formed areas. The three-dimensional field-effect transistor adequate selection algorithm in the integral three-dimensional structure which estimates local oxide influence is created. The algorithm estimates etching technologies, local oxidation process, and rational parameters and has feedback to other technological processes stages.